2005
DOI: 10.1152/jn.01179.2004
|View full text |Cite
|
Sign up to set email alerts
|

Coherence at 16-32 Hz Can Be Caused by Short-Term Synchrony of Motor Units

Abstract: of discharge times for pairs of motor units are used to infer the proportion of common synaptic input received by motor neurons. The physiological mechanisms that can produce the experimentally observed peaks in the cross-correlation histogram and the coherence spectrum are uncertain. The present study used a computational model to impose synchronization on the discharge times of motor units. Randomly selected discharge times of a unit that was being synchronized to a reference unit were aligned with some of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 55 publications
(89 reference statements)
2
12
0
Order By: Relevance
“…A similar relationship between synchronization and coherence was also observed by (Moritz et al, 2005) when motor unit synchronization was simulated by adjusting motor unit firing times by a specified delay. Adjustment of the individual motor unit discharge times to induce synchronization as in (Moritz et al, 2005) imposed a frequency modulation on the discharge times, similar to the effect of applying a shared motoneuron input signal as in the results presented here. In this study, coherence between motor units is introduced by the application of a common signal to two or more motor units, thereby enabling the observed coherence to be directly related to properties of the shared motoneuron input signals.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…A similar relationship between synchronization and coherence was also observed by (Moritz et al, 2005) when motor unit synchronization was simulated by adjusting motor unit firing times by a specified delay. Adjustment of the individual motor unit discharge times to induce synchronization as in (Moritz et al, 2005) imposed a frequency modulation on the discharge times, similar to the effect of applying a shared motoneuron input signal as in the results presented here. In this study, coherence between motor units is introduced by the application of a common signal to two or more motor units, thereby enabling the observed coherence to be directly related to properties of the shared motoneuron input signals.…”
Section: Discussionsupporting
confidence: 71%
“…Experimental studies have reported a significant positive correlation between motor unit synchronization and coherence between motor unit discharge times in the 15-30 Hz frequency range (Farmer et al, 1993;Kilner et al, 2002;Semmler et al, 2004). A similar relationship between synchronization and coherence was also observed by (Moritz et al, 2005) when motor unit synchronization was simulated by adjusting motor unit firing times by a specified delay. Adjustment of the individual motor unit discharge times to induce synchronization as in (Moritz et al, 2005) imposed a frequency modulation on the discharge times, similar to the effect of applying a shared motoneuron input signal as in the results presented here.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Semmler and Nordstrom 1998). Moreover, a computational model demonstrated that the imposition of motor unit synchronization causes a peak between 16 and 32 Hz in the coherence spectrum derived from the discharge times of pairs of motor units (Moritz et al 2005). The increase of heterogeneity of the spatiotemporal distribution of BB muscle activity, therefore, likely indicates a decrease in the strength of common input associated with motor unit synchronization.…”
Section: Discussionmentioning
confidence: 99%
“…For voluntary isometric contractions of fresh muscle, the prevailing view is that motor unit synchronization arises from common synaptic input received by motor neurons from either branched last-order interneurons or cortical efferents that receive common input (Datta et al 1991;Farmer et al 1990Farmer et al , 1993bMantel and Lemon 1987;Moritz et al 2005;Schmied et al 1999), but does not seem to be influenced by peripheral afferents (Farmer et al 1993a(Farmer et al , 1997. However, the mechanisms responsible for an increase in motor unit synchronization after eccentric exercise are less clear, because the exerciseinduced muscle damage is likely to cause physiological adjustments within the muscle that influence both the spinal and cortical control of movement.…”
Section: Motor Unit Synchronizationmentioning
confidence: 99%